(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This article explores the impact of automation on the roles of medical nurses and lab technicians in healthcare. Advancements in technology have led to significant changes in various aspects of patient care, including laboratory testing, electronic health records (EHR) integration, point-of-care testing (POCT), telemedicine, remote monitoring, and robotic assistance.